What Paves the Way to Conventional Language? The Predictive Value of Babble, Pointing, and Socioeconomic Status. Issue 1 (10th November 2016) - McGillion, Michelle; Herbert, Jane S.; Pine, Julian; Vihman, Marilyn; dePaolis, Rory; Keren‐Portnoy, Tamar; Matthews, Danielle
Abstract : A child's first words mark the emergence of a uniquely human ability. Theories of the developmental steps that pave the way for word production have proposed that either vocal or gestural precursors are key. These accounts were tested by assessing the developmental synchrony in the onset of babbling, pointing, and word production for 46 infants observed monthly between the ages of 9 and 18 months. Babbling and pointing did not develop in tight synchrony and babble onset alone predicted first words. Pointing and maternal education emerged as predictors of lexical knowledge only in relation to a measure taken at 18 months. This suggests a far more important role for early phonological development in the creation of the lexicon than previously thought.